The Degree of Effectiveness of Transformational Leadership in Improving the Organizational Innovation Level from Principals Perspective in Ajloun Governorate School - BanyAta, Mufid Mohammd Jamal (Journal of Educational and Psychological Sciences, 2022)
This Study aimed to identify the degree of effectiveness of transformational leadership in improving the organizational innovation level from principals perspective in Ajloun governorate school, the researcher used the Descriptive approaches, study Sample consisted from (90) Female and male principals, chosen randomly, to collect data Questioner used, which consisted (18) paragraph, the result of SPSS analysis shown that the degree of effectiveness of transformational leadership in improving the organizational innovation level from principals perspective in Ajloun governorate school was moderated with average (3.66 out of 5) , The finding also showed there is no statistically significant differences at (α≤0.05) refers to principal sex (male and female) in addition there were statistically significant differences refers to years of experience in favor of (11 years and more). The researcher recommends the necessity of paying attention to the work environment, and trying to create an environment that encourages leaders in national institutions to practice transformational leadership behaviors.